Incidental Thyroid Carcinoma in Patients Treated Surgically for Thyroid Disease - Sulaiman, Tharwat I; Hamid, Labeed S.; AbdulJabbar, Mohamad Q. (Journal of the Faculty of Medicine Baghdad, 2019)
Background: The occurrence of incidental thyroid cancer (ITC) has increased by three times during the last decades and this rise could be attributed to many factors. To limit the prevalence of ITC with goiter especially nodular goiter, total thyroidectomy can become a procedure of choice. Objective: To determine the extent of incidental thyroid carcinoma (ITC) and to plan a proper preoperative diagnostic work up and a convenient operative procedure for patients with different thyroid diseases. Results: ITC was found in 77 patients (19.15%). While, 63 patients with non-toxic MNG (15.6%), 12 patients with non-toxic solitary thyroid nodule (3%) and two patients (0.5%) with toxic MNG were observed in the study. Out of 77 patients with ITC, 56(72.7%) were ˂45 years and the remaining 21 (27.3%) ≥45 years. The 15 patients were males and 62 patients were females in these groups. Material and Methods: A prospective study was conducted during the period from October 2013 to October 2016 at Baghdad teaching hospital (main tertiary hospital in Iraq), first surgical unit by a single surgeon and his trainees. The study included 473 patients who were referred for surgical treatment of different thyroid diseases. About 71 patients were excluded from the study due to the diagnosis of malignancy (MNG) by FNAC or history of surgery. The remaining 402 patients were evaluated for the presence of the cancer by post-operative pathological examination. Conclusions: Although ITC in this study is relatively high especially in MNG; a more radical surgical treatment seems needed in the management of patients with presumably benign thyroid disease. The authors identify a potential benefit in performing total thyroidectomy instead of near or subtotal when considering management of MNG.